Clinical and dermoscopic assessment of patients with hypopigmented skin lesions - a cross - sectional study - Manisha Mareddy; Mamatha P.; Sruthi Kareddy (Galenos Publishing House, 2023)
Background and Design: Hypopigmentation refers to any form of decreased pigmentation and depigmentation. The study aims to evaluate the use of a dermatoscope in diagnosing cases of hypopigmented skin lesions. Materials and Methods: A total of 123 patients with hypopigmented skin lesions attending the dermatology outpatient department of a tertiary hospital were selected for the study. Dermoscopy was performed using DermLite-DL4 dermatoscope on hypopigmented lesions. Results: In vitiligo, a white glow on a white background with absent or reduced pigment network was characteristic. The characteristic pattern in Tinea versicolor was hypopigmented macules with a decreased pigment network against a brownish-white background and double-edged scales that furrowed in the skin lines. Idiopathic guttate hypomelanosis displayed a reduced pigment network with white structureless areas. Illdefined margins with uniformly reduced pigment networks against a brownish-white background with minimal white scales were characteristic of pityriasis alba. Follicular plugs, telangiectasias, rosette appearance, and peppered arrangement of grey-blue and brown globules are specific for lichen sclerosus ET atrophicus. Nevus depigmentosus showed a reduced reticular pigment network and feathery margins. Progressive macular hypomelanosis showed abrownish-white background, reticular pigment network, and minimal white scales in the skin lines. Ring scales and reticular pigment network were characteristic of polymorphous light eruption. Hypopigmented patches of leprosy showed a distorted light brown pigment network with a brownish-white background with minimal white scales, reduced eccrine and follicular openings, short broken hairs, v-shaped hairs, and pigtail hairs. Post-inflammatory hypopigmentation showed hypopigmented macules with decreased pigment network, white glow, perifollicular pigmentation, and peppered arrangement of grey-blue and brown globules. Chemical leukoderma is characterized by hypopigmented macules with blotchy erythema and grey granular dots. Hypopigmented lesions of systemic sclerosis revealed white homogeneous areas with perifollicular pigmentation. Conclusion: This study showed hypopigmented skin lesions might exhibit characteristic and specific dermoscopic features. When correlated with history and clinical examination, dermoscopy aids in diagnosing hypopigmented lesions and obviating the need for biopsy.